Lumbar spine bone mineral density in women breastfeeding for a period of 4 to 6 months: systematic review and meta-analysis - Ferreira, Larissa Brazolotto [UNESP]; Tirapeli, Keny Gonçalves [UNESP]; Silva, Carla Cristiane; Goldberg, Tamara Beres Lederer [UNESP] (Springer Nature, 2023)
Background: During the breastfeeding period, important transient changes in calcium homeostasis are verified in the maternal skeleton, to meet the demand for calcium for breastmilk production. The literature is inconclusive regarding the causes and percentages of involvement of bone densitometry resulting from exclusive breastfeeding (4 to 6 months). Methods: This article aims to systematically review the literature, to determine the occurrence, intensity, and factors involved in alterations in maternal bone mineral density (BMD), during a period of 4 to 6 months of exclusive breastfeeding. The search descriptors “woman”, “breastfeeding”, “human milk”, and “bone mineral density” were used in the electronic databases of the Virtual Health Library, Scielo (Scientific Electronic Library Online), CAPES Periodicals Portal, LILACS, Embase, PubMed/Medline, Cochrane, Scopus, and Web of Science in June 2023. Inclusion criteria for breastfeedingmothers were; aged to 40 years, primigravida, exclusively breastfeeding, with BMD assessments using dual-energy X-ray absorptiometry (DXA), with values expressed at baseline and from 4 to 6 months postpartum. The Jadad scale, Newcastle–Ottawa Scale, and Oxford Centre for Evidence-based Medicine – levels of evidence were adopted to assess the quality of the studies. For the meta-analytical study, statistical calculations were performed. Results: Initially, 381 articles were found using the search strategy and 26 were read in full. After risk of bias analysis, 16 articles remained in the systematic review and four were included in the meta-analysis. The studies showed a reduction in bone mass in the lumbar spine in the first months postpartum (4 – 6 months), when compared with a longer period of breastfeeding (12–18 months). The breastfeeding group presented a greater impact in the meta-analysis than the control group (non-breastfeeding, pregnant, or immediate postpartum), with a reduction in BMD in the lumbar spine of -0.18 g/cm2 (-0.36, -0.01 g/cm2); 95% Confidence Interval, on a scale from 0 to 10. Conclusions: Our results demonstrated a transitory reduction in bone densitometry of the lumbar spine during exclusive breastfeeding for 4 to 6 months, which was gradually restored later in the postpartum period. More prospective studies are needed to better understand the topic. Trial registration: PROSPERO platform (nº CRD42021279199), November 12th, 2021.
Keywords: Bone mineral density; Breastfeeding; Lactation